Implementasi Algoritma Variable Length Binary Encoding Untuk Kompresi File Gambar - Simarmata, Laura Marselly (STMIK Budi Darma, 2024)
Compression is a way to reduce large file. Sometimes, when downloading image, they take up a lot of space in storage and use up a lot of data quota. This can be a problem because storage space is limited and data quota is also limited. So, use compression to reduce image file so they don’t take up a lot of storage space and save data quota when sending. In this research, the compression process will use the Variable Length Binary Encoding algorithm to compress image file. A system will be implemented for image file compression and the compression performance will be measured using compression parameters, namely Ratio of Compression (Rc), Compression of Ratio (Cr), and Space Saving with the format used for image file being JPG. Implementation and performance measurement of image file compression found that the Ratio of Compression (Rc) using the Variable Length Binary Encoding algorithm produced 3.63 bits, and a Compression Ratio is 27.5%, and Space Saving of is 72.5%. From the results of system design and testing using Microsoft Visual Studio 2008, the image file compression application design was successfully compressed to a smaller size of 4.37 KB, and testing of the decompression process was successfully carried out using the Variable Length Binary Encoding algorithm.